Improving Supply Chain Efficiency for Local Coffee Producers in Toraja Utara - Yusrijal, Yusrijal; Fadillah, Dian; Rina, Rina (Journal Development Manecos, 2025)
A research examines the essential elements which determine the efficiency of supply chains operated by local coffee manufacturers in Toraja Utara, Indonesia. The research analyzed supply chain performance by gathering quantitative data from 150 Toraja Utara local coffee producers concerning supplier relations and inventory control and transportation systems and information distribution. Supplier relationships together with inventory management emerge as leading determinants for supply chain efficiency and produce strong positive links to performance outcome assessment. The predictor that delivers the highest impact on supply chain performance is supplier relationships (r = 0.62, p < 0.01) while inventory management (β = 0.29, p < 0.01) holds the second position. The research shows a significant link between transportation logistics (r = 0.48, p < 0.01) and information sharing (r = 0.42, p < 0.01) and efficiency however physical limitations in logistics reduce their effectiveness. Studies regarding agricultural supply chains gain new insights through this research because it focuses on smallholder coffee producers in a developing country environment that receives limited academic attention. The findings enable practitioners to apply supplier partnership enhancement and inventory control optimization in supply chain management. This evidence points to the requirement of upgrading basic facilities which must include better communication systems and transportation networks. Efficient local coffee supply chains in Indonesia can be improved through the findings which guide policymakers and industry stakeholders to enhance performance.